Improving High School Students' Interpersonal Communication Skills through Collaborative Learning: An Experimental Study - Sofi, Sofi; Ansor, Jumadi; ohan Lusia , Miswantoro (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2025)
This study aims to test the effectiveness of collaborative learning on improving students' communication skills, including empathy, active listening, and negotiation skills. The analysis was conducted using ANCOVA with pretest scores as covariates. The results showed that collaborative learning treatment had a significant effect on improving posttest results (F = 83.487, p < 0.001) with a partial eta squared value of 0.416, indicating a large contribution of treatment to the dependent variable. The discussion of the results shows consistency with empirical findings in the last six years which confirm that interactions in collaborative learning strengthen students' social and academic competencies. Furthermore, implications for teachers, curriculum, and professional training are discussed, emphasizing the importance of strengthening teacher capacity in designing adaptive curriculum-based collaborative activities. The conclusion of this study states that collaborative learning is a relevant pedagogical strategy to improve students' communication skills in the 21st century education era. Structured teacher policies and training are needed to ensure the sustainability of its implementation in elementary schools. This study provides theoretical and practical contributions to the development of learning innovations that focus on strengthening students' affective and social